ANALISIS STATUS KESEHATAN MENSTRUASI DENGAN TINGKAT KELETIHAN REMAJA DI SALAH SATU WILAYAH DI KABUPATEN BANDUNG TAHUN 2022 - Mulyati, Iceu; Sri Lestari; Meda Yuliani (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
Menstruation is a monthly cycle that occurs in a woman, menstruation in adolescents is the main feature of puberty which indicates that the reproductive system has started to function properly. whether there is a relationship between menstrual health status and the level of fatigue in adolescents. The research method used is quantitative analysis with a cross sectional approach with data collection using questionnaires and direct Hb examination, the results of the study show that anemia and dismenore are the main factors that have a relationship directly with fatigue during menstruation the impact of this fatigue will cause a decrease in the ability of adolescents, especially in the learning process so that learning achievement also decreases, for this reason it is necessary to make efforts to deal with complaints or problems during menstruation. One of the management of anemia in adolescents can be by giving blood-added tablets, while menstrual pain can be managed with complementary methods such as consuming herbal drinks, acupressure or other measures.